1977
DOI: 10.1002/ana.410020210
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin‐Secreting pituitary tumors

Abstract: Prolactin secretion was evaluated in 69 patients with pituitary tumors. Among the 47 w h o were seen prior to treatment, hyperprolactinemia was present in 37 (79%). Excluding patients with galactorrhea, hyperprolactinemia was present in 19 (70%) of those seen before treatment. T h e r e was little correlation between tumor size and level of serum prolactin. Both transsphenoidal surgery and radiotherapy greatly reduced the hyperprolactinemia, b u t a more rapid decrease was achieved with microsurgical removal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
3

Year Published

1979
1979
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(13 citation statements)
references
References 15 publications
2
8
0
3
Order By: Relevance
“…Thus, a 20 min Prl response after 200 ug TRH higher than 3.5 times the basal level was never observed in our tumour patients and only 5 out of 42 patients (12%) showed a peak level higher than 2 times the basal level (R2 > 1). This is again in accordance with the results re¬ ported by others; irrespective of the dose of TRH used, the response of tumour patients does not exceed the 3.5 times basal value Snyder et al 1974;Zarate et al 1975;Jacobs et al 1976;Glass et al 1976;Fossati et al 1976;Kletzky et al 1977;Kleinberg et al 1977;Lobo Antunes et al 1977;Corbey et al 1977;Samaan et al 1977;Silvestrini et al 1978;Cowden et al 1979;Jeske 1979). Only Lamberts et al (1976) observed in 4 out of 24 patients a higher response; however, these authors used a higher (400 ug) dosage of TRH, which may have caused a greater response.…”
Section: Resultssupporting
confidence: 88%
“…Thus, a 20 min Prl response after 200 ug TRH higher than 3.5 times the basal level was never observed in our tumour patients and only 5 out of 42 patients (12%) showed a peak level higher than 2 times the basal level (R2 > 1). This is again in accordance with the results re¬ ported by others; irrespective of the dose of TRH used, the response of tumour patients does not exceed the 3.5 times basal value Snyder et al 1974;Zarate et al 1975;Jacobs et al 1976;Glass et al 1976;Fossati et al 1976;Kletzky et al 1977;Kleinberg et al 1977;Lobo Antunes et al 1977;Corbey et al 1977;Samaan et al 1977;Silvestrini et al 1978;Cowden et al 1979;Jeske 1979). Only Lamberts et al (1976) observed in 4 out of 24 patients a higher response; however, these authors used a higher (400 ug) dosage of TRH, which may have caused a greater response.…”
Section: Resultssupporting
confidence: 88%
“…Although symptoms of hypogonadism are still the most prevalent, symptoms due to mass effects commonly serve as those that prompt medical attention and lead to the diagnosis. A summary of 16 series comprising 444 men with prolactinomas indicates that 77.9% were impotent, 36.6% had visual field defects, 33.8% had partial or complete hypopituitarism, 29.1% complained of headaches, and only 10.9% had galactorrhea (60, 64,75,85,114,115,[431][432][433][434][435][436][437][438][439][440][441]. Thus, about one third of men have symptoms due to tumor size.…”
Section: A Prolactinomas In Malesmentioning
confidence: 99%
“…Nevertheless, the size of the tumor, regardless of whether functioning or not, is obviously one of the most important determining factors of the overall cure rate ( Antunes et al 1977, Chang et al 1977, Hardy et al 1978, Jaquet et al 1978, Tindal et al 1978, Derome et al 1979, Murray et al 1979, Post et al 1979, Pelkonen et al 1981. Nevertheless, the size of the tumor, regardless of whether functioning or not, is obviously one of the most important determining factors of the overall cure rate ( Antunes et al 1977, Chang et al 1977, Hardy et al 1978, Jaquet et al 1978, Tindal et al 1978, Derome et al 1979, Murray et al 1979, Post et al 1979, Pelkonen et al 1981.…”
mentioning
confidence: 99%